Pengembangan Model Inovasi Bahan Ajar Pendidikan Agama Islam Berbasis Aplikasi Canva di SMK Alwashliyah Jakarta: Penelitian - Kurniawan, Jefri; Fariiz, Abdurrahman; Safiuddin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to develop digital-based Islamic Religious Education (PAI) teaching materials using the Canva application to improve learning effectiveness at SMK Al Washliyah Jakarta. The background of the study is based on the low interest and motivation of students in PAI due to unattractive conventional learning methods and the lack of visual media. The study used a Research and Development (R&D) approach with the ADDIE development model that includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included PAI teachers and 11th-grade students of the AKL, MP1, and MP2 programs. Data collection instruments consisted of interviews, questionnaires, and tests. The results of expert validation showed that the Canva teaching materials had a "very feasible" level of feasibility with an average score of 97%. Testing on students showed an increase in understanding of Islamic concepts and enthusiasm for learning. This study concluded that Canva-based digital teaching materials can be an innovative solution for creating interactive, engaging, and relevant PAI learning to meet the needs of the times.